2018
DOI: 10.1172/jci.insight.96910
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular hemolysis activates complement via cell-free heme and heme-loaded microvesicles

Abstract: In hemolytic diseases, such as sickle cell disease (SCD), intravascular hemolysis results in the release of hemoglobin, heme, and heme-loaded membrane microvesicles in the bloodstream. Intravascular hemolysis is thus associated with inflammation and organ injury. Complement system can be activated by heme in vitro. We investigated the mechanisms by which hemolysis and red blood cell (RBC) degradation products trigger complement activation in vivo. In kidney biopsies of SCD nephropathy patients and a mouse mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
130
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 144 publications
(144 citation statements)
references
References 56 publications
6
130
0
2
Order By: Relevance
“…Hemolysis‐derived products or anti‐endothelial antibodies present in the serum could explain this activation. This complement over activation is concordant with the complement‐mediated cytotoxicity from SCD patients' sera (modified Ham's test), the enhanced C3 deposits on ECs exposed to SCD RBC microvesicles, and the endothelial C3 deposits in tissues of SCD mice and biopsies of patients . This over activation is indeed at least in part heme‐dependent since it was inhibited by the heme scavenger hemopexin.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Hemolysis‐derived products or anti‐endothelial antibodies present in the serum could explain this activation. This complement over activation is concordant with the complement‐mediated cytotoxicity from SCD patients' sera (modified Ham's test), the enhanced C3 deposits on ECs exposed to SCD RBC microvesicles, and the endothelial C3 deposits in tissues of SCD mice and biopsies of patients . This over activation is indeed at least in part heme‐dependent since it was inhibited by the heme scavenger hemopexin.…”
Section: Discussionsupporting
confidence: 65%
“…The mechanism of this complement activation is not yet fully elucidated. in vitro studies and mouse models have provided evidence that the activation of the cascade in SCD could proceed by different mechanisms: on ischemic tissue, via cell‐free heme/heme‐carrying RBC microvesicles, or directly on the surface of the SCD RBCs . The clinical relevance of the progression of the complement cascade to its terminal steps has not been investigated in detail in a large cohort of SCD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Merle et al found C3b/iC3b and C5b‐9 deposits in the kidneys of SCD patients and two mouse models of SCD, including Townes mice as confirmed here. They induced intravascular hemolysis or injection of heme or hemoglobin in WT mice to provide evidence that these complement deposits could be triggered by cell‐free heme . Heme and heme‐loaded microvesicles induced activation of the alternative complement pathway and heme triggered endothelial expression of P‐selectin, C3aR and C5aR and down regulation of CD46.…”
Section: Discussionmentioning
confidence: 99%
“…Ischemia‐reperfusion physiology underpins SCD biology when vessels are transiently occluded in organs throughout the body and subsequently reopened . In this ischemia‐reperfusion paradigm, the innate immune system plays a key role in promoting the inflammatory response, which includes TLR4 signaling and complement activation …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation